Diagnostic accuracy of tumor markers for malignant pleural effusion: a derivation and validation study - Zhai, Kan; Wang, Wen; Wang, Yao; Liu, Jing-Yuan; Zhou, Qiong; Shi, Huan-Zhong (Journal of Thoracic Disease, 2017)
Background: The utility of tumor markers (TMs) for differentiating malignant pleural effusion (MPE) from benign pleural effusion (BPE) has been a subject of controversy. The majority of published studies are single center designed and lack validation. We performed a derivation and validation study in China to evaluate the diagnostic value of carcinoembryonic antigen (CEA) as well as carbohydrate antigen (CA) 15-3, CA 19-9 and CA 125 to differentiate between MPE and BPE. Methods: Three hundred and twenty seven pleural effusion (PE) and paired serum samples were collected from consecutive patients with MPE or BPE in Beijing (174 patients, derivation) and Wuhan (153 patients, validation) during the same period. The concentrations of four TMs were tested using chemiluminescent microparticle immunoassay technology. The performance of the TMs was analyzed by standard receiver operating characteristic (ROC) curves. Results: The levels of four TMs were significantly higher in MPE than in BPE and the corresponding serum. The concentrations of CEA and CA 15-3 were more stable than the concentrations of CA 125 and CA 19-9. CEA was the best single marker for discriminating MPE from BPE. With a specificity of 100% in the total population, the highest sensitivity (37.8%) using serum was found in CEA. In addition, CEA presented 19.8% sensitivity in PE and 18.0% sensitivity in the ∆(PE–serum). For CA 15-3, the sensitivity was 32.4% in PE, 15.3% in the PE/serum ratio and 25.2% in the ∆(PE–serum). Conclusions: CEA and CA 15-3 rather than CA 125 and CA 19-9 are more reliable to differentiate between MPE and BPE. The use of the ∆(PE–serum) value in TMs, such as CEA and CA 15-3, may improve the sensitivity and specificity of the diagnosis etiology of PE.